Timely insertion of AMPA receptor in developing vestibular circuits is required for manifestation of righting reflexes and effective navigation. (February 2023) - Lai, Suk-King; Wu, Kenneth Lap Kei; Ma, Chun-Wai; Ng, Ka-Pak; Hu, Xiao-qian; Tam, Kin-Wai; Yung, Wing-Ho; Wang, Yu Tian; Wong, Tak Pan; Shum, Daisy Kwok-Yan; Chan, Ying-Shing
Abstract: Vestibular information processed first by the brainstem vestibular nucleus (VN), and further by cerebellum and thalamus, underlies diverse brain function. These include the righting reflexes and spatial cognitive behaviour. While the cerebellar and thalamic circuits that decode vestibular information are known, the importance of VN neurons and the temporal requirements for their maturation that allow developmental consolidation of the aforementioned circuits remains unclear. We show that timely unsilencing of glutamatergic circuits in the VN by NMDA receptor-mediated insertion of AMPAR receptor type 1 (GluA1) subunits is critical for maturation of VN and successful consolidation of higher circuits that process vestibular information. Delayed unsilencing of NMDA receptor-only synapses of neonatal VN neurons permanently decreased their functional connectivity with inferior olive circuits. This was accompanied by delayed pruning of the inferior olive inputs to Purkinje cells and permanent reduction in their plasticity. These derangements led to deficits in associated vestibular righting reflexes and motor co-ordination during voluntary movement. Vestibular-dependent recruitment of thalamic neurons was similarly reduced, resulting in permanently decreased efficiency of spatial navigation. The findings thus show that well-choreographed maturation of the nascent vestibular circuitry is prerequisite for functional integration of vestibular signals into ascending pathways for diverse vestibular-related behaviours. Highlights: Unsilencing of NMDAR-only synapses in the vestibular nucleus at postnatal day 5–7 enables integration of inputs into ascending pathways. Delayed unsilencing hinders pruning of inputs to Purkinje cells and reduces plasticity, impacting postural and motor coordination. Such delay impairs cerebellar and thalamic connectivity of vestibular inputs into adulthood, with impacts on spatial cognition.